2002
DOI: 10.1161/01.cir.0000030184.70207.ff
|View full text |Cite
|
Sign up to set email alerts
|

High Doses of Vitamin C Reverse Escherichia coli Endotoxin–Induced Hyporeactivity to Acetylcholine in the Human Forearm

Abstract: Background-Acute inflammation causes endothelial vasodilator dysfunction that may be mediated by oxidative stress. Methods and Results-In this randomized, double-blind, crossover study, forearm blood flow responses to acetylcholine (ACh) (endothelium-dependent dilator) and glyceryl-trinitrate (GTN) (endothelium-independent dilator) were assessed before and after induction of acute systemic inflammation by low doses of Escherichia coli endotoxin (LPS) (20 IU/kg IV) in 8 healthy volunteers. The acute effect of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
71
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 41 publications
13
71
2
1
Order By: Relevance
“…In previous studies, we have demonstrated that increased oxidative stress plays an important role in vascular dysfunction during inflammation. In those studies, 14,15 LPS-induced hyporeactivity to ACh and to different vasoconstrictors could be reversed by intra-arterial infusion of high doses of the antioxidant vitamin C. Despite the lack of a direct antioxidative effect, statins may inhibit key proteins involved in generation of reactive oxygen species. Experimental studies revealed that statins inhibit production of superoxide via the NADPH oxidase system in monocytes, 26 neutrophils, 27 and endothelial cells, 28 because activation of NADPH oxidase is dependent on an isoprenoid group, ie, geranyl geraniol, which derives from HMG-CoA and is thus inhibited by statins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, we have demonstrated that increased oxidative stress plays an important role in vascular dysfunction during inflammation. In those studies, 14,15 LPS-induced hyporeactivity to ACh and to different vasoconstrictors could be reversed by intra-arterial infusion of high doses of the antioxidant vitamin C. Despite the lack of a direct antioxidative effect, statins may inhibit key proteins involved in generation of reactive oxygen species. Experimental studies revealed that statins inhibit production of superoxide via the NADPH oxidase system in monocytes, 26 neutrophils, 27 and endothelial cells, 28 because activation of NADPH oxidase is dependent on an isoprenoid group, ie, geranyl geraniol, which derives from HMG-CoA and is thus inhibited by statins.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of LPS to humans has been established by other groups and at our institution as a model to study cardiovascular responses to acute systemic inflammation. 13,14,16,17 This dose of LPS impairs the vascular responses to adrenergic vasoconstrictors and endotheliumdependent vasodilators, with maximum clinical effect and vascular hyporeactivity Ϸ4 hours after LPS administration. 13,14 Therefore, FBF experiments were repeated at 4 hours after LPS administration.…”
Section: Study Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…66 Actually, higher levels of oxidized LDL have been associated to endothelial-dependent vascular dysfunction in patients with coronary heart disease 6 and in patients with cardiovascular risk factors. 78 Moreover, Pleiner et al 79 have shown that IEDD induced by the administration of lipopolysaccharide in normal subjects can be restored by the local administration of high doses of Vitamin C, a free-radical scavenger. This suggests that oxidative stress may play an important role in inflammation-induced IEDD.…”
mentioning
confidence: 99%